Fuzheng Nizeng Decoction regulated ferroptosis and endoplasmic reticulum stress in the treatment of gastric precancerous lesions: A mechanistic study based on metabolomics coupled with transcriptomics - Chu, Ying-Ming; Wang, Ting-Xin; Jia, Xiao-Fen; Yang, Yao; Shi, Zong-Ming; Cui, Guang-Hui; Huang, Qiu-Yue; Ye, Hui; Zhang, Xue-Zhi (Frontiers in Pharmacology, 2022)
Background: Fuzheng Nizeng Decoction (FZNZ) has a history of decades in gastric precancerous lesions (GPL) treatment, which has shown clear clinical efficacy. Blocking GPL is a key measure to reduce the incidence of gastric cancer (GC). Therefore, we aim to investigate the mechanism of FZNZ-induced ferroptosis and endoplasmic reticulum (ER) in MNNG-induced gastric precancerous lesion (MC) cells, which has been rarely studied in Traditional Chinese Medicine (TCM). Methods: First, CCK8 and lactate dehydrogenase assays were conducted to study the potential effect of FZNZ on MC cells. Second, combined transcriptomic and metabolomic analysis were used to explore the effect and mechanism of FZNZ. Functionally, the occurrence of ferroptosis was assessed by transmission electron microscopy morphological observation and measurement of ferrous iron levels, lipid peroxidation, and glutathione levels. Finally, the expression levels of mRNAs or proteins related to ferroptosis and ER stress were determined by qPCR or western blot assays, respectively. Results: FZNZ inhibited MC cells viability and induced cell death. By metabolomics coupled with transcriptomics analysis, we found that the mechanism of FZNZ treatment induced ferroptosis and was related to glutathione metabolism and ER stress. We then, for the first time, found that FZNZ induced ferroptosis, which contributed to an increase in intracellular ferrous iron, reactive oxygen species, and malondialdehyde and a decrease in glutathione. Meanwhile, the protein level of glutathione peroxidase 4 (GPX4) was decreased. The mRNA levels of ATF3/CHOP/CHAC1, which are related to ferroptosis and ER stress, were also upregulated. Conclusion: Our results elaborate that FZNZ could induce ferroptosis and ER stress in MC cells, and reduce GPX4/GSH. ATF3/CHOP/CHAC1 may play a crosstalk role, which provides a new molecular mechanism for the treatment of GPL.